Predator exclusion and riverine input: Effects on sub-Arctic intertidal soft-bottom macrobenthos - Frederike Hoppmann; Bodil A. Bluhm; Rolf Gradinger; Christian Buschbaum; Maeve McGovern; Markus Molis (Journal of Experimental Marine Biology and Ecology, 2026)

Physiological costs of infection by the invasive parasitic copepod Mytilicola intestinalis accumulate across temporal scales in the blue mussel Mytilus edulis - Felicitas Demann; Christian Buschbaum; Christian Bock; Gaël Guillou; Benoit Lebreton; Gisela Lannig; Markus Molis; K. Mathias Wegner (Journal of Invertebrate Pathology, 2025)

A horizon scan for Arctic coastal biodiversity research: understanding changes requires international collaboration - Jakob Thyrring; Philippe Archambault; Michael Burrows; Katrin Iken; Fernando P. Lima; Joana Micael; Markus Molis; Catia Monteiro; Sergej Olenin; Paul E. Renaud; Ricardo A. Scrosati; Rui Seabra; et al. (Trends in Ecology & Evolution, 2025)

Effects of a Wave Power Park with No-Take Zone on Decapod Abundance and Size - Anke Bender; Olivia Langhamer; Markus Molis; Jan Sundberg (Journal of Marine Science and Engineering, 2021)
Past studies have revealed higher levels of biodiversity, total abundance, and size of individuals around offshore installations of renewable energy. This study investigated the effects of Lysekil wave power park (area 0.5 km2) on the abundance and carapace size of decapods at the Swedish west coast. For that purpose, decapods were caught with cages during four consecutive summers. Two types of cages were applied to catch a wide range of decapod species and sizes. The abundance and size of decapods were not significantly different within the wave power park and up to a distance of 360 m outside of it. The catch rate, i.e., number of decapods caught in 24 h, was not significantly different among sampling locations but revealed inter-annual variation for both cage types. The results suggest a limited role of the incidental no-take zone of the small Lysekil wave power park on the abundance and size of local decapods. However, neither were negative impacts, such as decreasing abundances or smaller carapace sizes, discovered. As an increase in the number of marine renewable energy production sites is foreseen, a scaled-up and larger study addressing MPA networks and other environmental interactions should be considered.

Effects of Detached Seaweeds on Structure and Function of Arctic Intertidal Soft-Bottom Communities - María José Díaz; Christian Buschbaum; Paul E. Renaud; Markus Molis (Frontiers in Marine Science, 2021)
Expected lower sea-ice cover and increased storm frequency have led to projections of an increase in seaweed detritus in Arctic marine systems in the near future. To assess whether detached seaweed affects structural and functional traits of species assemblages in soft-bottom habitats, comparable experiments were run in two intertidal sites (Longyearbyen and Thiisbukta) on Svalbard. At each site, we fixed nets containing the locally dominating seaweeds Saccharina latissima and Desmarestia aculeata (Thiisbukta) or Fucus sp. (Longyearbyen) to intertidal mud flats. Empty nets were fixed as procedural controls at both sites. After 2.5 months, one sediment core was taken from each manipulated plot and the number of individuals, dry mass, and average length of each encountered animal taxon were recorded. The same measurements were taken from cores collected from unmanipulated areas at each site, both at the start and end of the experiment. Abundance data were used to calculate estimates of diversity (Shannon-index, evenness, and taxon richness), while initial and final average length measurements were used to estimate taxon-specific growth. Log response ratios of initial and final abundance in unmanipulated areas were used to estimate magnitude and direction of the effect of change in community traits over time, serving as a reference to log response ratios estimating manipulated seaweed effects. In Longyearbyen, the presence of detached seaweeds reduced abundance and dry mass by, on average, 46 and 70%, respectively, compared to unmanipulated benthic communities. In Thiisbukta, the presence of seaweeds enhanced evenness, on average by 16%, but reduced abundance and growth of benthic fauna by, on average, 31 and 86%, respectively. Seaweed effects were generally smaller in Thiisbukta than in Longyearbyen. At both sites, time effects were generally opposite in direction to those caused by the seaweed treatments, yet of similar or larger magnitude. Through reversing temporal dynamics of several of the tested community traits, detached seaweeds strongly modified the structure and functioning of soft-bottom species assemblages at both intertidal sites. We suggest that the detected effects possibly result from seaweed-induced changes in environmental conditions and/or physical disturbance as underlying processes.

Disturbance effects of kelp thalli on structure and diversity of a coastal Arctic marine soft-bottom assemblage - Sina Petrowski; Markus Molis; Anke Bender; Christian Buschbaum (Polar Biology, 2016)

Do bioturbation and consumption affect coastal Arctic marine soft-bottom communities? - Sina Petrowski; Markus Molis; Katrin Schachtl; Christian Buschbaum (Polar Biology, 2016)

A predator has nonconsumptive effects on different life-history stages of a prey - Julius A. Ellrich; Ricardo A. Scrosati; Camilla Bertolini; Markus Molis (Marine Biology, 2016)

Predator nonconsumptive effects on prey recruitment weaken with recruit density - Julius A. Ellrich; Ricardo A. Scrosati; Markus Molis (Ecology, 2015)
We investigated the nonconsumptive effects (NCEs) of predatory dogwhelks ( Nucella lapillus ) on intertidal barnacle ( Semibalanus balanoides ) recruitment through field experiments on the Gulf of St. Lawrence coast and the Atlantic coast of Nova Scotia, Canada. We studied the recruitment seasons (May–June) of 2011 and 2013. In 2011, the Gulf coast had five times more nearshore phytoplankton (food for barnacle larvae and recruits) during the recruitment season and yielded a 58% higher barnacle recruit density than the Atlantic coast at the end of the recruitment season. In 2013, phytoplankton levels and barnacle recruit density were similar on both coasts and also lower than for the Gulf coast in 2011. Using the comparative–experimental method, the manipulation of dogwhelk presence (without allowing physical contact with prey) revealed that dogwhelk cues limited barnacle recruitment under moderate recruit densities (Atlantic 2011/2013 and Gulf 2013) but had no effect under a high recruit density (Gulf 2011). Barnacle recruits attract settling larvae through chemical cues. Thus, the highest recruit density appears to have neutralized dogwhelk effects. This study suggests that the predation risk perceived by settling larvae may decrease with increasing recruit density and that prey food supply may indirectly influence predator NCEs on prey recruitment.

Comparing the ability of a non-indigenous and a native seaweed to induce anti-herbivory defenses - Hee Young Yun; Markus Molis (Marine Biology, 2012)

Comparison of the impacts of consumers, ambient UV, and future UVB irradiance on mid‐latitudinal macroepibenthic assemblages - MARKUS MOLIS; MARTIN WAHL (Global Change Biology, 2009)
Future levels in ultraviolet‐B (UVB) radiation are expected to increase directly due to stratospheric ozone depletion and under water indirectly by, for example, global warming effects on DOC concentrations, altered trophic interactions in the plankton, or reduced eutrophication. While detrimental UV effects have been reported at the cellular level, little to nothing is known about community‐wide effects of ambient and future UVB radiation. In a 4‐month field experiment, the ambient UV regime was (i) reduced by cut‐off filters which removed either UVB or total UV from the solar spectrum or (ii) increased to predicted future levels by UVB lamps. To allow relating the effects of present and future UV regimes to another important ecological control of community structure and diversity in subtidal marine habitats, consumer effects were quantified by an exclusion treatment under ambient light regimes. Ambient UV regimes did not affect community structure, biomass accrual, and diversity. In contrast, under enhanced UVB levels, the dominance of the competitively superior blue mussels increased and species richness and biomass accrual decreased. Species composition of the assemblages differed between the two UV regimes. Effects of enhanced UVB radiation and of consumption on biomass accrual, diversity, and structure of the community were comparable in magnitude and timing, but of opposite direction. In contrast, the effects of enhanced UVB radiation on growth and abundance of mussels were in the same direction, but shorter and weaker than consumer effects. Most UV effects were transitory and vanished within the first 2 months of succession. Our results indicate that present and future UVB levels may be of limited importance and not stronger in effect size than other ecological controls in structuring the shallow‐water low‐diversity macrobenthic communities in temperate regions.

Do sulphuric acid and the brown alga Desmarestia viridis support community structure in Arctic kelp patches by altering grazing impact, distribution patterns, and behaviour of sea urchins? - Markus Molis; Hendrik Wessels; Wilhelm Hagen; Ulf Karsten; Christian Wiencke (Polar Biology, 2009)

Natural succession of macroalgal-dominated epibenthic assemblages at different water depths and after transplantation from deep to shallow water on Spitsbergen - Anna Fricke; Markus Molis; Christian Wiencke; Nelson Valdivia; Annelise S. Chapman (Polar Biology, 2008)

Influence of disturbance and nutrient enrichment on early successional fouling communities in an oligotrophic marine system - João Canning‐Clode; Manfred Kaufmann; Markus Molis; Martin Wahl; Mark Lenz (Marine Ecology, 2008)
Disturbance and productivity are often cited as the main factors determining temporal and spatial patterns in species distribution and the diversity of communities. A field experiment was conducted to test the role of these factors in the structuring of early successional fouling communities in a nutrient limited system at the south coast of Madeira Island. Macro‐benthic sessile communities, established on artificial settlement substrata, were manipulated and surveyed over a 9‐week period. We applied mechanical disturbances of four different frequencies crossed with three levels of inorganic nutrient enrichment. Fertilization enhanced community diversity by favouring the establishment and growth of macroalgae. Disturbance reduced diversity by eliminating species – but only at the highest nutrient level. This is explained by a multiple‐stressor model; species most sensitive to nutrient deficiency (only present in the highest enrichment treatment) were simultaneously the most sensitive to disturbance.

Ultraviolet radiation and consumer effects on a field‐grown intertidal macroalgal assemblage in Antarctica - KATHARINA ZACHER; ANGELA WULFF; MARKUS MOLIS; DIETER HANELT; CHRISTIAN WIENCKE (Global Change Biology, 2007)
Ultraviolet radiation (UVR) research on marine macroalgae has hithero focussed on physiological effects at the organism level, while little is known on the impact of UV radiation on macroalgal assemblages and even less on interactive effects with other community drivers, e.g. consumers. Field experiments on macrobenthos are scarce, particularly in the Antarctic region. Therefore, the effects of UVR and consumers (mainly limpets were excluded) on early successional stages of a hard bottom macroalgal community on King George Island, Antarctica, were studied. In a two‐factorial design experimental units [(1) ambient radiation, 280–700 nm; (2) ambient minus UVB, 320–700 nm and (3) ambient minus UVR, 400–700 nm vs. consumer–no consumer] were installed between November 2004 and March 2005 ( n = 4 plus controls). Dry mass, species richness, diversity and composition of macroalgal assemblages developing on ceramic tiles were followed. Consumers significantly suppressed green algal recruits and total algal biomass but increased macroalgal richness and diversity. Both UVA and UVB radiation negatively affected macroalgal succession. UVR decreased the density of Monostroma hariotii germlings in the first 10 weeks of the experiment, whereas the density of red algal recruits was significantly depressed by UVR at the end of the study. After 106 days macroalgal diversity was significantly higher in UV depleted than in UV‐exposed assemblages. Furthermore, species richness was significantly lower in the UV treatments and species composition differed significantly between the UV‐depleted and the UV‐exposed treatment. Marine macroalgae are very important primary producers in coastal ecosystems, serving as food for herbivores and as habitat for many organisms. Both, UVR and consumers significantly shape macroalgal succession in the Antarctic intertidal. Consumers, particularly limpets can mediate negative effects of ambient UVR on richness and diversity till a certain level. UVB radiation in general and an increase of this short wavelength due to stratospheric ozone depletion in particular may have the potential to affect the zonation, composition and diversity of Antarctic intertidal seaweeds altering trophic interactions in this system.

Ultraviolet radiation shapes seaweed communities - Kai Bischof; Ivan Gómez; Markus Molis; Dieter Hanelt; Ulf Karsten; Ulrike Lüder; Michael Y. Roleda; Katharina Zacher; Christian Wiencke (Reviews in Environmental Science and Bio/Technology, 2006)

Variability in grazer-mediated defensive responses of green and red macroalgae on the south coast of South Africa - Eliecer Díaz; Christine Güldenzoph; Markus Molis; Christopher McQuaid; Martin Wahl (Marine Biology, 2006)

UV effects that come and go: a global comparison of marine benthic community level impacts - Martin Wahl; Markus Molis; Andrew Davis; Sergey Dobretsov; Simone T. Dürr; Josefin Johansson; Jeff Kinley; David Kirugara; Matthias Langer; Heike K. Lotze; Martin Thiel; Jeremy C. Thomason; et al. (Global Change Biology, 2004)
Ambient UV radiation has substantially increased during the last decades, but its impact on marine benthic communities is hardly known. The aim of this study was to globally compare and quantify how shallow hard‐bottom communities are affected by UV during early succession. Identical field experiments in 10 different coastal regions of both hemispheres produced a consistent but unexpected pattern: (i) UV radiation affected species diversity and community biomass in a very similar manner, (ii) diversity and biomass were reduced to a larger extent by UVA than UVB radiation, (iii) ambient UV levels did not affect the composition of the communities, and (iv) any UV effects disappeared during species succession after 2–3 months. Thus, current levels of UV radiation seem to have small, predictable, and transient effects on shallow marine hard‐bottom communities.